Linear Volterra Integro-Differential Second-Order Equations Unresolved with Respect to the Highest Derivative - Kopachevsky, Nikolay Dmitrievich; Syomkina, Ekaterina Vladimirovna (Eurasian Mathematical Journal, 2013)
We consider the Cauchy problem for Volterra integro-differential second-order linear equations which describe an evolution of dynamical systems with infinite numbers of degrees of freedom taking into account relaxation effects. Existence theorems for strong solutions for three classes of complete integro-differential second-order equations are obtained.